2020
DOI: 10.1021/acsomega.0c01566
|View full text |Cite
|
Sign up to set email alerts
|

Cecal Butyrate (Not Propionate) Was Connected with Metabolism-Related Chemicals of Mice, Based on the Different Effects of the Two Inonotus obliquus Extracts on Obesity and Their Mechanisms

Abstract: Obesity is a metabolic disease and causes significant changes in host and gut microbial metabolite levels. However, little research has been done on the relationship between host and gut microbial metabolites. Thus, this study investigated the connection of the chemicals, based on the different effects of two Inonotus obliquus extracts on high-fat-diet-induced mice and their mechanisms. In this study, C57BL6/J mice fed with a high-fat diet were given I. obliquus et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 48 publications
(84 reference statements)
1
11
0
Order By: Relevance
“…As a new type of medicinal fungus, chaga possesses antitumor, antioxidant, hypoglycemic, and hypolipidemic effects ( Wang et al, 2017b ; Yu et al, 2020 ; Duru et al, 2019 ; Burmasova et al, 2019 ; Lu et al, 2021 ). In recent years, the use of medicinal fungi in the treatment of kidney disease has been widely examined ( Zhong et al, 2015 ; Wang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a new type of medicinal fungus, chaga possesses antitumor, antioxidant, hypoglycemic, and hypolipidemic effects ( Wang et al, 2017b ; Yu et al, 2020 ; Duru et al, 2019 ; Burmasova et al, 2019 ; Lu et al, 2021 ). In recent years, the use of medicinal fungi in the treatment of kidney disease has been widely examined ( Zhong et al, 2015 ; Wang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been reported that chaga extracts could reduce the blood lipid level, lipid accumulation, and body weight in DKD mice induced by the high-fat diet ( Yu et al, 2020 ). This is consistent with the result of the present study that the body weights of the two intervention groups were lower than that of the DKD model group.…”
Section: Discussionmentioning
confidence: 99%
“…The sample treatment method, NMR data acquisition and processing were performed using previously described methods [ 29 ]. The raw data were preprocessed using MestReNova 10.0.…”
Section: Methodsmentioning
confidence: 99%
“…IOP (containing 78.27% polysaccharide) was obtained by hot water extraction, 80% ethanol precipitation, protein removal, and ethanol cleaning, and IOE (containing 27.86% polyphenols and 38.55% triterpenoids) was extracted by 80% ethanol after removing impurities with hot water (Yu et al., 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Inonotus obliquus ethanol extract (IOE) is rich in polyphenols and triterpenes, and the I. obliquus polysaccharides (IOP) are rich in polysaccharides. The two extracts had different effects on obese individuals due to different active ingredients (Yu et al., 2020). In this paper, we compare the effects of the two extracts on HFD mice at four temporal points (weeks 0, 2, 8, and 14) to explore more potential mechanisms.…”
Section: Introductionmentioning
confidence: 99%